TEKNIK MULTISLICE COMPUTED TOMOGRAPHY (MSCT) CERVICAL PADA KASUS TRAUMA - Seftiana, Aning; R, Khalifah; Nur Fadhilah, Lina (Perhimpunan Radiografer Indonesia (PARI), 2021)
Background: Cervical trauma is a very common injury of severity and varying prognosis. Cervical CT Scan is an examination of the cervical spine including other tissues using the MSCT tool to find out the anatomy on the cervical spine with axial, sagittal, coronal. The purpose of this study was to know the technique and result of cervical MSCT images in case trauma. Methods: This type of research is library research (library research), which is a series of research related to the method of collecting library data or research where the object of research is explored through a variety of library information (books, proceedings, articles, and scientific journals). Literature research or literature review is research that critically examines or reviews the knowledge, ideas, or findings contained in the academic-oriented literature, and formulates theoretical and methodological contributions to certain topics. The focus of the literature research that the author has done is related to the Cervical Multislice Computed Tomography (MSCT) technique in cases of trauma. Results: Based on the results of images on MSCT cervical trauma cases to obtain anatomical information that is able to show the firm boundaries of the corpus lamina, spinosus process, tranverse process, and fragment fracture, using axial, sagittal, and coronal slice recontruction. Conclusions : Based on a review of several journal literature, the cervical MSCT examination technique in trauma cases used a 64 x collimation 0.6 mm, with axial section reconstruction of 1 mm thickness, coronal and sagittal sections of 1.5 mm thickness, 3D, and volume rendering. In severe polytrauma patients the technique is performed with the addition of an intravenous contrast material. The results of images on MSCT cervical trauma cases to obtain anatomical information that is able to show the firm boundaries of the corpus, lamina, spinous process, transverse process, and fragment fractures, using axial, sagittal, and coronal slice reconstruction.